2022
DOI: 10.1016/j.cmet.2021.12.024
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 suppresses alcohol consumption through an amygdalo-striatal circuit

Abstract: Highlights d An FGF21 analog suppresses alcohol consumption in nonhuman primates d The FGF21 co-receptor KLB is expressed in cells in the basolateral amygdala (BLA) d FGF21 signals to KLB BLA/NAc -projecting neurons to suppress alcohol consumption d FGF21 suppresses sucrose and alcohol consumption through distinct circuits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 54 publications
(78 reference statements)
2
49
0
Order By: Relevance
“…In fact, the human KLB gene is associated with alcohol intake, and Klb deletion in mice can increase alcohol preference (Schumann et al., 2016; Talukdar et al., 2016). This is consistent with work demonstrating that FGF21 can suppress alcohol intake in mice (Schumann et al., 2016; Søberg et al., 2018; Talukdar et al., 2016; Flippo et al, 2022). Therefore, the amygdala may be a target site for FGF21 activity that reinforces alcohol aversion.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, the human KLB gene is associated with alcohol intake, and Klb deletion in mice can increase alcohol preference (Schumann et al., 2016; Talukdar et al., 2016). This is consistent with work demonstrating that FGF21 can suppress alcohol intake in mice (Schumann et al., 2016; Søberg et al., 2018; Talukdar et al., 2016; Flippo et al, 2022). Therefore, the amygdala may be a target site for FGF21 activity that reinforces alcohol aversion.…”
Section: Discussionsupporting
confidence: 89%
“…This “ NEFA-PPAR-FGF21-LPL ” axis is particularly intriguing in light of thinking that obesity and related diseases may represent an “FGF21-resistant” state analogous to insulin resistance [ 92 , 93 , 94 , 95 ] and with paradoxically high FGF21, and could operate alongside promising efforts to develop FGF21-directed therapy to treat atherogenic dyslipidemia, diabetes, and NAFLD [ 96 , 97 ]. Exploring FGF21 dynamics, as well as the FGF21/FGF1 ratio that has been proposed to regulate lipolysis [ 98 , 99 ] (and even the possible impact of FGF21 on carbohydrate and sugar taste preferences [ 100 ] and alcohol consumption [ 101 ]), in LMHR as part of the LEM, could provide insight into hormonal mechanisms of metabolic disease.…”
Section: Lipoprotein Lipase Regulatorsmentioning
confidence: 99%
“…To address these gaps, Flippo and colleagues 1 investigated the effects of FGF21 and a long-acting FGF21 analog (PF-05231023) on alcohol consumption in rodents and non-human primates. They first showed that in mice, alcohol consumption increased circulating FGF21 levels, selective FGF21 deletion from the liver increased alcohol use, and intraperitoneal administration of recombinant human FGF21 dose-dependently reduced alcohol consumption.…”
Section: Main Textmentioning
confidence: 99%
“…Further, the authors showed that KLB deletion in the BLA blocked FGF21's ability to suppress alcohol consumption, highlighting the necessity of FGF21 signaling in the BLA for alcoholrelated effects. Of note, previous studies found KLB expression in other brain regions, including the suprachiasmatic nucleus, nucleus solitary tract, and the hypothalamus, 6 to be involved in feeding and metabolic functions of FGF21, while BLA appears to play a key role in FGF21's effects on alcohol seeking behaviors (e.g., deletion of KLB in the BLA had no effect on FGF21's ability to suppress sucrose intake 1 ).…”
mentioning
confidence: 91%
See 1 more Smart Citation